Safety and tolerability of long-term apomorphine infusion in advanced Parkinson's disease: an Indian multi-center (APO-IND) experience - Metta, Vinod; Dhamija, Rajinder K.; Batzu, Lucia; Mrudula, Rukmini; Kumar, Natuva Sai Sampath; S., Arunan; Falup-Pecurariu, Cristian; Rodriguez-Blazquez, Carmen; Goyal, Vinay; L.K., Prashanth; Bhattacharya, Kalyan; Kumar, Suresh; et al. (Scientific reports, 2023)
Advanced Parkinson’s Disease (APD) is complicated by the emergence of motor and non-motor fluctuations, which are initially predictable and eventually become unpredictable, in part due to erratic gastric absorption and short half of oral levodopa. Attempts to manage such fluctuations with oral dopaminergic drugs often lead to disabling dyskinesias. Continuous Subcutaneous Apomorphine Infusion (CSAI), despite being approved for the treatment of APD since 1993, was approved in India only in 2019. We studied the safety, tolerability and efficacy of CSAI in Indian patients with APD in a registry design to raise local awareness of this important treatment. We conducted a prospective registry-based observational audit at 10 centers across different states of India. Patients with APD, not responding to or with significant side effects from oral dopaminergic therapy, were assessed at baseline and at month 6 and 12 following CSAI infusion. Fifty-one patients completed the study, CSAI significantly reduced the functional impact of dyskinesia (p < 0.01 at 6 months and p < 0.001 at 12 months). There was a significant improvement in the OFF-state from baseline (p < 0.01 at 6 months and p < 0.001 at 12 months) No discernible side effects were observed apart from mild site reaction (n = 7), nausea (n = 7) skin nodules (n = 2). CSAI demonstrated safety, efficacy, tolerability and improved quality of life in patients with APD, as shown in previous studies. Our study highlighted current existing inequalities in treatment availability, lack of awareness, knowledge gap, affordability and cost remains a concern regarding apomorphine use in Indian PD population.